Strengthening Intellectual Property Rights: Legal Responses to Trademark Counterfeiting in Indonesia’s E-Commerce Era (CV. Era Digital Nusantara, 2025)
This research examines legal protection against the unauthorized use of counterfeit trademarks in Indonesia under Constitution Number 20 of 2016 concerning Brands and Geographical Indications (MIG Law). The study addresses significant challenges arising from the circulation of counterfeit goods, which causes economic losses of up to Rp 291 trillion, tax revenue losses, and employment disruptions. With the rise of e-commerce and digital platforms, counterfeiters exploit technological advancements to distribute fake products widely, complicating enforcement efforts. The research objectives include analyzing the comprehensive legal framework for trademark protection, evaluating enforcement mechanisms, and identifying effective dispute resolution routes. The study employs a qualitative approach, reviewing relevant legislation, enforcement data, and stakeholder perspectives. Key findings reveal that while the MIG Law provides a strong statutory basis, enforcement remains constrained by procedural requirements such as the necessity of owner complaints to trigger criminal proceedings. Non-litigation alternatives like mediation and arbitration offer viable dispute resolution but depend on effective implementation. Criminal enforcement is notably more effective in securing counterfeit goods than civil litigation. The study recommends legal reforms to empower authorities for proactive actions without owner complaints and the enhancement of human resource capabilities, including IP investigator training and mediator certification. In conclusion, strengthening both legal provisions and institutional capacity is essential for robust protection of registered trademarks against counterfeiting in Indonesia’s evolving digital economy.